2018
DOI: 10.2147/jhc.s147098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of loco-regional treatment for hepatocellular carcinoma prior to living donor liver transplantation: a report from a single center in Egypt

Abstract: Background and aimThe number of loco-regional therapies (LRTs) for hepatocellular carcinoma (HCC) has increased dramatically during the past decade, bridging or downstaging patients on the waiting list for liver transplantation. This study aimed to analyze the outcomes of LRTs prior to living donor liver transplantation in patients with HCC.MethodsSixty-two HCC patients received living donor liver transplantation at Ain Shams Center for Organ Transplantation over a 2-year period. Data from 29 HCC patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that when locoregional therapy was effective enough to render the tumor completely necrotic, the results after LT were good [ 44 , 45 , 46 ]. However, imaging examinations often overestimate the therapeutic effect compared to histopathological findings [ 47 , 48 , 49 , 50 ]. Rubinstein et al [ 51 ] reported that 77% of patients had viable tumors even though imaging examinations showed complete response (CR).…”
Section: Bridging Therapy To Liver Transplantationmentioning
confidence: 99%
“…It has been reported that when locoregional therapy was effective enough to render the tumor completely necrotic, the results after LT were good [ 44 , 45 , 46 ]. However, imaging examinations often overestimate the therapeutic effect compared to histopathological findings [ 47 , 48 , 49 , 50 ]. Rubinstein et al [ 51 ] reported that 77% of patients had viable tumors even though imaging examinations showed complete response (CR).…”
Section: Bridging Therapy To Liver Transplantationmentioning
confidence: 99%